Association between Serum Zinc Level and Cutaneous Viral Warts: A Case Control Study - Annu Ranjit; Sudharshan Lal Rajbhandari; Narayan Gautam; Yogesh Poudyal (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Cutaneous viral warts are one of the common skin disorders in general population which can affect any age group and any gender in any country and pose a significant health problem. A possible association with zinc has been suggested in previous studies. Zinc is known to be required for efficient functioning of immune system.